Uji Diagnostik Filariasis Menggunakan Rapid Diagnostic Test (RDT) Brugia malayi terhadap Pemeriksaan Mikroskopis di Desa Buntoi Kabupaten Gunung Mas, Provinsi Kalimantan Tengah - Gadis Rinaty Susanty; Hernayanti Hernayanti; Dwi Sarwani Sri Rejeki (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2021)
Gunung Mas Regency, Central Kalimantan Province is one of the endemic filariasis areas with Microfilaria rate of 3.4%. One of the efforts made to control this problem is Mass Drug Administration once a year for 5 years. Currently, the Rapid Diagnostic Test (RDT) method is being developed, a quick and easy diagnostic technique to detect the presence of parasites in the patient's body. This study aims to determine the results of the filariasis diagnostic test using the Brugia malayi RDT on the microscopic examination in Buntoi Village, Gunung Mas Regency, Central Kalimantan Province. This research is a descriptive study with a cross-sectional approach with the research subjects all residents of Buntoi Village with inclusion and exclusion criteria totaling 161 samples. Collecting data was carried out by examination and interviews with questionnaires. Data analysis by calculating the microfilaria rate, sensitivity and specificity and calculating the frequency distribution of research variables. Data is presented in percentage form and displayed in tabular form. The results of the diagnostic study of B. malayi RDT and the microscopic examination were the same, i.e all were negative and no microfilariae were found. The diagnostic test for filariasis RDT Brugia malayi on microscopic examination (SDJ) obtained 0% sensitivity, 100% specificity, 0% Positive Predictive Value and 100% Negative Predictive Value. The level of public knowledge about filariasis includes 61% good category, knowledge of MDA 40% good category and knowledge about prevention of filariasis in good category 53%.